Youth, Faith and Environmental Consciousness in Africa: A Research Imperative for Youth Ministry within Practical Theology - Beukes, Jacques Walter (Stellenbosch theological journal, 2021)
Climate change and environmental degradation are arguably among the most significant concerns for humanity and environmental sustainability on a worldwide scale. Cultivating a multidimensional environmental consciousness that connects emotional and cognitive environmental knowledge with environmentally sustainable practises is a potential method for addressing ecological concerns on an individual basis. This could potentially lead to an impact on policy-making procedures at the local, national, regional, and global levels. Today's youth are at the epicentre of discussions about ecological (in) justice, environmental consciousness, and climate change discourses and practices. This is illustrated by international protests including the Fridays for Future and Extinction Rebellion campaign, to highlight a few. However, both of the aforementioned youth movements are western illustrations of youths who are participating in these discourses. The paper focuses on how African youth shape environmental consciousness, as well as how African theological institutions and their theological curricula (i.e., youth ministry modules) are geared toward shaping environmental consciousness (particularly among youth) within the African context. Within the practical theology discipline, the tripartite concern with the link between youth, religion, and environmental conscience has been under-researched. This study highlights a new purposeful endeavour to investigate the nexus between youth, faith, and environmental consciousness in Africa.